Study guides

☆☆

Q: Solve 2X plus 3 equal 9 X?

Write your answer...

Submit

Related questions

2x + 3 is an expression that is already in simplest form; you cannot "solve" it.

3(2x+5 ) = 39

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4

3

-2x+2

2x+3 = 7 2x = 7-3 2x = 4 x = 2

2x+3 = -11 2x = -11-3 2x = -14 x = -7

2x+3=9x =>3=7x =>3/7=x

2x + 3 = 9 2x = 6 x = 3

2x + 3 = x 2x + 3 - 3 = x - 3 2x = x - 3 2x - x = x - 3 - x x = -3

6 + 2x =2(3 + x)

3x+4 = 2x-3 3x-2x = -3-4 x = -7

3x-2 = 2x+3 3x-2x = 3+2 x = 5

It is 3.

2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!

2x+3 = 9x 3 = 9x-2x = 7x 7x = 3 x = 3/7

2x+3y=40-2x+2y=20Since 2x does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 2x from both sides.3y=-2xDivide each term in the equation by 3.(3y)/(3)=-(2x)/(3)Simplify the left-hand side of the equation by canceling the common terms.y=-(2x)/(3)if you were solving for x It would be x=-(3y)/2

2x + 2/3= 5/3 2x= 3/3 2x=1 x=1/2

2x + 3 = 92x = 9 - 32x = 6x = 6/2x = 3

3x + 2x = 5x

If we assume that it equals zero and you wish to solve for x, then the answer is:-x2 + 2x - 3 = 0x2 - 2x + 3 = 0x2 -2x + 1 = -2(x - 1)2 = -2x - 1 = ± √(-2)x = 1 ± i√2

If 2x + 5 = 11, then 11 - 5 = 2x 6 = 2x 3 = x

x+3(x+1)=2x x + 3x + 3 = 2x 2x + 3 = 0 2x = -3 or x = -1.5

Plug and chug! 14 + 2(1) - 4(3) 14 + 2 - 12 = 4 ====

You can do the equation Y 2x plus 3 on a graph. On this graph the Y would equal 5 and X would equal to 0.